1966
DOI: 10.1136/hrt.28.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different degrees of tilt on cardiac output, heart rate, and blood pressure in normal man.

Abstract: Many workers have shown that the cardiac output in normal man is less in the upright than in the recumbent position (McMichael and SharpeySchafer, 1944;Stead et al., 1945;Coe, Best, and Lawson, 1950;Wang, Marshall, and Shepherd, 1960;Chapman, Fisher, and Sproule, 1960;Reeves et al., 1961). The physiological events underlying this change are complex and depend on many variables, such as the angle of tilt and length of time the patient remains at a given angle and whether the change is from recumbency to an upri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
28
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 9 publications
8
28
1
Order By: Relevance
“…The diastolic blood pressure rises normally after tilting [9]. Here a lack of rise was shown in diabetics with retinopathy.…”
Section: Discussionmentioning
confidence: 90%
“…The diastolic blood pressure rises normally after tilting [9]. Here a lack of rise was shown in diabetics with retinopathy.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, several important issues can be addressed. In normal individuals, the gravitational stress of head up tilt is associated with peripheral pooling ofblood, reduction ofvenous return, and subsequent reduction of cardiac output (37,38). To protect and maintain blood pressure, head up tilt stimulates baroreceptor mechanisms that result in an increase of heart rate and systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models and in humans have demonstrated abnormalities of sympathetic and parasympathetic control of heart rate in chronic congestive heart failure. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Few data are available regarding the effects of vasodilator therapy on these abnorrnalities, although this mode of therapy is widely used. '6 Vasodilator therapy could significantly alter the vasoconstriction, volume alterations and hormonal response that normally accompany the assumption of upright posture.…”
mentioning
confidence: 99%